Chronic pancreatitis. Issue 6 (June 2016) - French, Jeremy J.; Charnley, Richard M.
Abstract: Chronic pancreatitis is distinguished by structural and functional criteria. Alcohol is the major aetiological factor, but about 20% of patients have another cause such as hereditary pancreatitis. Abdominal pain is the usual presenting feature, often as recurrent attacks of acute pancreatitis but chronic pancreatitis may be clinically silent. The pathogenesis of chronic pancreatitis is incompletely understood. Diagnosis is usually made on imaging (CT, magnetic resonance cholangiopancreatography, endoscopic ultrasound). Complications include exocrine and endocrine insufficiency, obstructive jaundice, duodenal obstruction, left-sided portal hypertension, and the development of pancreatic cancer. Overall management is difficult and depends upon symptoms, morphological characteristics and complications. Treatment options include medical, endoscopic, and surgical strategies; the latter is reserved for patients with complications. Early involvement of a specialist centre in the care of patients with complicated chronic pancreatitis is important and should be encouraged.